2005
DOI: 10.1902/jop.2005.76.2.303
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandins E2 and F Enhance Differentiation of Cementoblastic Cells

Abstract: We conclude that PGE(2) and PGF(2alpha) exert an anabolic effect on OCCM mineralization through activation of PKC signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(34 citation statements)
references
References 30 publications
2
31
1
Order By: Relevance
“…PGF 2a has been shown to induce the differentiation of cementoblasts and stimulate the matrix metalloproteinase activity as well as IL-6 production of gingival fibroblasts (10,11,31). In this study, exposure to PGF 2a stimulates IL-8 production of pulp cells.…”
Section: Discussionmentioning
confidence: 57%
“…PGF 2a has been shown to induce the differentiation of cementoblasts and stimulate the matrix metalloproteinase activity as well as IL-6 production of gingival fibroblasts (10,11,31). In this study, exposure to PGF 2a stimulates IL-8 production of pulp cells.…”
Section: Discussionmentioning
confidence: 57%
“…PGE 2 is one of the most important signaling molecules produced by the cells. Although PGE 2 , has been related to bone resorption during the early inflammatory phase, it also may contribute to attenuate the inflammatory reaction and induce healing process at a later stage, because many studies have also reported an anabolic effect of this prostanoid in bone and also in periodontal tissues (Keller et al 1993;Marks and Miller 1994;RamiresYanes et al 2005;Camargo et al 2005). PGE 2 action is mediated through four subtype receptors belonging to the G-protein-couple receptor family (EP1, EP2, EP3 and EP4).…”
Section: Introductionmentioning
confidence: 99%
“…Locally delivered PGE 1 increases the formation of alveolar bone, PDL and cementum in adult dogs (18). IL-1 inhibits mineralization by an immortalized cementoblastic cell line (OC-CM cells) while PGE 2 and PGF 2α have an anabolic effect on mineral nodule formation by OC-CM cells (19). Fluprostenol (flup), a synthetic prostanoid agent with a molecular structure similar to PGF 2α , exerts a well-defined, dose-dependent anabolic effect on mineralization by OC-CM cells (19).…”
Section: Introductionmentioning
confidence: 99%
“…IL-1 inhibits mineralization by an immortalized cementoblastic cell line (OC-CM cells) while PGE 2 and PGF 2α have an anabolic effect on mineral nodule formation by OC-CM cells (19). Fluprostenol (flup), a synthetic prostanoid agent with a molecular structure similar to PGF 2α , exerts a well-defined, dose-dependent anabolic effect on mineralization by OC-CM cells (19). While this anabolic effect appears to be, in part, mediated by activation of the protein kinase C (PKC) signaling pathway (19), the exact molecular mechanism of the prostanoid-induced mineralization by OC-CM cells is not well understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation